SOCIAL-POLITICAL CONDITIONS AFTER THE BONGAYA TREATY OF 1667; ISLAMIC POLITICAL PERSPECTIVE - Arif, Muhammad; Mundzir, Chaerul; Ramadhani, Is Hamdan (Al-Risalah Jurnal Ilmu Syariah dan Hukum, 2021)
This article aimed to describe the socio-political conditions after the Bongaya Treaty of 1667. This study employed the historical research method (library research). The researcher applied several approaches, namely the historical approach, religious approach, anthropological approach, and sociological approach. The Makassar War is a momentum for change from all aspects, not only changes from the political aspect but also the social, cultural and economic aspects that greatly tormented the people of Gowa. As a King, Sultan Hasanudin was responsible for the fate of the royal people of Gowa, which was getting sad. Sultan Hasanudin had to consider this even though he wanted to continue to fight. Sultan Hasanudin really understood the suffering of the people of the Kingdom of Gowa. Due to these considerations, the war lasted approximately four years, starting from 1666-1669 and ending with the Bungaya Treaty, which consisted of 30 articles. The treaty affected all aspects of Gowa community life, not only in terms of political factors but also the existence of Muslims. Since then, the power and influence of the Netherlands in East Indonesia began to be embedded towards serious colonialism. Sultan Hasanuddin, who dashed to defend his country until the last second has controlled the Kingdom of Gowa for 16 years; namely 1653-1669 and died in Gowa on June 12, 1670.